Annie Ernaux and the Writing of Traces in The Years and The Super 8 Years - de Paiva Vieira, Miriam; Machado, Thalisson (Revista (Entre Parênteses), 2025)
This article investigates the intersections between the novel The Years (2008), by Annie Ernaux, and the documentary The Super 8 Years (2022), by Annie Ernaux and David Ernaux-Briot, in order to explore the relationship between subjective and objective memory through different media. Based on the concept of autosociobiography, the study analyzes how the author transforms personal experiences into collective testimony, connecting individual memory to social history. Drawing on media archaeology, it examines how audiovisual and written records preserve and reframe the past. The analysis shows that memory, though rooted in intimate experience, is key to the construction of historical narratives, acting as a link between subjectivity and broader historical contexts.